2020
DOI: 10.1101/2020.02.13.935304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RootDigger: a root placement program for phylogenetic trees

Abstract: In phylogenetic analysis, it is common to infer unrooted trees. Thus, it is unknown which node is the most recent common ancestor of all the taxa in the phylogeny. However, knowing the root location is desirable for downstream analyses and interpretation. There exist several methods to recover a root, such as midpoint rooting or rooting the tree at an outgroup. Non-reversible Markov models can also be used to compute the likelihood of a potential root position. We present a software called RootDigger which use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Our results suggest that non-reversible amino-acid models are more useful for inferring root positions than non-reversible DNA models, which is consistent with results from previous simulations using the NR-DNA model (Bettisworth and Stamatakis 2020). One explanation for this difference between the NR-DNA and the NR-AA models is the bigger character-state space of the NR-AA models.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results suggest that non-reversible amino-acid models are more useful for inferring root positions than non-reversible DNA models, which is consistent with results from previous simulations using the NR-DNA model (Bettisworth and Stamatakis 2020). One explanation for this difference between the NR-DNA and the NR-AA models is the bigger character-state space of the NR-AA models.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, since non-reversible models naturally incorporate a notion of time, the position of the root on the tree is a parameter that is estimated as part of the ML tree inference. Since the incorporation of non-reversible models in efficient ML tree inference software is relatively new , we still understand relatively little about the ability of non-reversible models to infer the root of a phylogenetic tree, although a recent simulation study has shown some encouraging results (Bettisworth and Stamatakis 2020).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Rooting with RootDigger. To further assess the uncertainty of the root location via a mathematically distinct approach, we also performed analyses with our RootDigger tool (40).…”
Section: Data Preparation and Analysis Pipelinementioning
confidence: 99%